Εξάρθρωση δικτύου παράνομης διακίνησης μεταναστών από το Λ.Σ. - ΕΛ.ΑΚΤ. (Κως, 20-04-2021) (HellenicCoastguard, 2021)
: Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE